Visiting a Neighborhood of Medieval Silves Using Virtual Reality and Non-Player Characters - Antunes, Rui (Mimesis Journal, 2024)
We present a virtual reality (VR) project where a medieval neighbourhood was digitally recreated using advanced 3D technology. In collaboration with the Museum of Silves and with University of Lisbon students, the initiative sought to revive a section of the historic Xilb (medieval Silves in Portugal) through a 3D/VR simulation with AI-driven virtual characters. The simulation featured autonomous characters (nonplayer characters) and dynamic events, offering an immersive experience. The article highlights insights gained from visitors’ immersive encounters with the simulated medieval streets of Xilb and their virtual inhabitants, emphasizing the potential of such approaches for connecting individuals to collective memory and cultural heritage, while acknowledging associated responsibilities.